INFORMATION ASYMMETRY AND DIVIDEND POLICY IN THE CEMENT SUB-SECTOR MANUFACTURING COMPANY - Devika Putrihadiningrum; Sumani (Jurnal Mantik, 2022)
The purpose of this research is to analyze the effect of information asymmetry on dividend policy in manufacturing companies in the cement sub-sector. The research used is explanatory research,Proof of the hypothesis is done by testing the regression coefficients partially. The results in this study explain as follows: this study shows that asymmetric information proxied by earnings forecast error has no significant negative effect on dividend policy. The second hypothesis in this study shows that asymmetric information proxied by firm size has no significant positive effect on dividend policy. The third hypothesis in this study shows that asymmetric information proxied by growth opportunities has a significant positive effect on dividend policy. The fourth hypothesis in this study shows that asymmetric information which is proxied by earnings forecast error, firm size, growth opportunities have a significant effect on dividend policy. The magnitude of the influence of Asymmetric Information on dividend policy is 54.7%, of which another 45.3% is influenced by other asymmetric information proxies which are not discussed in this study.